Characterization of Therapeutic Targets from Aspergillus fumigates in response to Adjunctive Combination Therapy (Ketoconazole with EDTA) - Ruhil, Sonam; Kumar, Vikash; Malik, Monika; Balhara, Meenakshi; Chhillar, Anil K. (Anti-Infective Agents, 2022)
Background: The Kingdom (Fungi) comprises numerous species that are associated with numerous fungal diseases. Moreover, the fungal resistance, stagnation in the development of antifungal agents and unacceptably high mortality rate associated with some resistant fungus indicate that alternative therapeutic options should be considered. Objective: The objective of this study was to find out new therapeutic targets of A.fumigatus in response to adjunctive combination, i.e., Ketoconazole (KTZ) plus EDTA. Methods: A.fumigatus was cultured in the absence and presence of a sublethal dose (MIC 50) of EDTA, KTZ and a combination of KTZ plus EDTA. The cytosolic proteins were extracted by mechanical grinding of fungal cells. The protein profile was studied by using a proteomic approach and the identification of protein was done by MALDI-TOF/MS. The morphological effect of the combination on A. fumigatus was studied by Scanning Electron Microscopy (SEM) and toxic effect on erythrocytes by haemolytic assay. Results: The combination of KTZ with EDTA was non-toxic up to 500 μg/ml by MTT assay. It inhibits the expression of the following proteins: Glutamatedehydrogenase, Phenyl alanyl t-RNA synthetase POD G, CaO19-5601, AN6454.2 (Conserved domain; MFS (Major Facilitator Superfamily), serine/threonine-protein kinase and dipeptidyl peptidase (identified by peptide mass fingerprinting). Some of these proteins are involved in hyphal development. Morphological defects on the development of fungus (like disrupted hyphal tips, phialide) were observed. Conclusion: These targets can be used for novel drug development as some of them are involved in fungal virulence, and adjunctive combination therapy can be an optimistic approach.
Keywords: adjunctive combination